Financial Literacy and Tasawuf Values as Determinants of Financial Behavior Among Food Market Traders: Evidence from Pasar Ciawi, Tasikmalaya Regency - Sani Haryati; Iis Amanah Amida (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
Sound financial management remains a persistent challenge among food market traders in Indonesia, where limited financial knowledge and underdeveloped spiritual self-regulation often coexist. Drawing on data from 30 purposively selected traders at Pasar Ciawi, Tasikmalaya Regency, this study examines how financial literacy and tasawuf values —two theoretically distinct yet practically interrelated constructs— shape traders' financial behavior. A quantitative survey design was adopted, employing a five-point Likert instrument validated through Pearson correlation (r-table = 0.361) and assessed for internal consistency via Cronbach's Alpha. Multiple linear regression served as the primary analytical tool. Findings reveal that financial literacy exerts a pronounced positive effect on financial behavior (β = 0.703; t = 9.472; p < .001), whereas tasawuf values fall short of statistical significance at the partial level (β = −0.056; t = −0.702; p = .488).